Prevalence of hepatitis A, B, C and D infections in the Juruti municipal hospital, western Pará, Brazil - Marceliano Nunes, Heloisa (2010)
The Juruti Municipality, located to the west of the Pará State, possesses major bauxite reserves, the exploration of which started in 2005. The appearance of some diseases and the increased frequency of others have been influenced by this exploration, particularly in relation to viral hepatitis. These epidemiological trends are different from those observed anywhere else worldwide. To define the prevalence of the infections by the hepatitis A, B, C and D viruses in the Juruti municipal hospital between February 2007 and April 2008, serum samples were collected from patients and analyzed for serological markers of hepatitis A (HAV), B (HBV), C (HCV) and D (HDV) by immunoenzymatic techniques. In samples positive for the hepatitis B and C viruses, assays were performed for the detection of HBV-DNA and HCV-RNA by PCR and RT-PCR, respectively. Among the 1,630 samples collected, the prevalence of total anti-HAV was 85.6%; HBsAg was 0.7%; anti-HBc/anti-HBs was 9.1% and isolated anti-HBs were 31.4%. Among the HBsAg+, 9.1% were HBeAg+; 63.6% were anti-HBe+ and 72.7% were HBV-DNA+. Anti-HCV was positive in 0.1% of the samples and positive serologies were not detected for HDV Laboratory-based characterization revealed a high prevalence of infection by HAV, detected chronic HBV carriers and those susceptible to HBV, identified an HCV carrier and revealed the absence of HDV carriers. Local, community-based epidemiological studies are recommended for comparison to the hospital data presented here.